Factors Affecting Purchasing Behavior on Chinese Investors in Real Estate in Thailand - Zhou, Xuezhen; Dowpiset, Kitikorn; Khlaewkhla, Sansanee Aranyanak (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2023)
Purpose: This study investigates the factors affecting purchase behavior on Chinese investors of real estate in Thailand after the postepidemic. Through indepth research and analysis, the researcher put forward attitudes, subjective norms, perceived behavioral control, and finance impact on Chinese investors’ purchase of real estate in Thailand. The effect of purchase intention was specifically examined. Research design, data and methodology: The sampling techniques used in this research are convenience sampling and snowball sampling, as well as quantitative methods of multiple linear regression. Results: The target population of this study is potential Chinese investors in Globally. The researchers distributed a total of 400 questionnaires to unknown target of potential Chinese investors via WeChat. Therefor, 300 valid questionnaires were collected. Conclusions: The research result shows that subjective norms, attitudes, and perceived behavioral control affecting the intention to purchase a housing. However, the finance factor is significantly weaker in affecting the intention of Chinese investors to purchase real estate in Thailand.